Adhesive composition, adhesive layer, and polarizing plate with adhesive
A (meth)acrylic resin-based adhesive composition with a specific ionic compound addresses antistatic and metal corrosion issues in polarizing plates, ensuring strong adhesion and corrosion resistance for image display devices.
Patent Information
- Application Number
- JP2024088907
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-08
- Filing Date
- 2024-05-31
- Publication Date
- 2024-12-19
AI Technical Summary
Existing adhesive compositions used in polarizing plates for image display devices do not adequately provide antistatic properties and metal corrosion prevention, particularly for thin metal layers with narrow line widths, leading to issues like pitting corrosion.
A pressure-sensitive adhesive composition containing a (meth)acrylic resin with specific structural units and an ionic compound, comprising an anion moiety and organic cation, is developed to enhance antistatic properties and prevent metal corrosion.
The adhesive composition achieves good adhesive strength, effective antistatic performance, and robust metal corrosion prevention, especially for thin metal layers and narrow line widths, thereby improving the durability of image display devices.
Smart Images

Figure 2024177099000021 
Figure 2024177099000022 
Figure 2024177099000023
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, and a polarizing plate with a pressure-sensitive adhesive. [Background technology]
[0002] Polarizing plates are widely used in image display devices. Examples of image display devices include liquid crystal display devices and organic EL display devices. Polarizing plates are distributed in a state in which a transparent protective film is laminated on both sides or one side of a polarizer, an adhesive layer is formed on at least one surface, and a release film is attached to the adhesive layer. In addition, a retarder is laminated on a polarizing plate in a state in which a protective film is attached to both sides or one side of a polarizer to form an elliptical polarizing plate, and an adhesive layer is formed on the retarder side. Before being attached to an image display device, the release film is peeled off from the adhesive layer on the surface of these polarizing plates, elliptical polarizing plates, and retarders, and the polarizing plates are attached to the image display device via the exposed adhesive layer. When the release film is peeled off, static electricity is generated between the adhesive surface and the release film in such polarizing plates, elliptical polarizing plates, or retarders, and the polarizing plates are attached to the image display device before the static electricity attenuates, which may cause problems such as the image display device being destroyed by the static electricity.
[0003] As one of the countermeasures, Patent Document 1 below proposes using, as the adhesive, a composition containing an ionic conductive composition composed of an electrolyte salt and an organopolysiloxane, and an acrylic copolymer, in a polarizing plate in which a protective film is laminated on the surface of a polarizer film and an adhesive layer is provided on the surface of the protective film.
[0004] In addition, the following Patent Document 2 discloses an antistatic acrylic adhesive containing an acrylic copolymer having a hydroxyl group and an alkylene oxide chain such as an ethylene oxide chain in the side chain, an ionic compound, and a curing agent. In Patent Document 2, an ionic compound having an inorganic cation such as a Li salt is used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-313807 [Patent Document 2] JP 2005-206776 A Summary of the Invention [Problem to be solved by the invention]
[0006] Metal wiring is used in the display element, touch panel element, etc. of the image display device. When an ionic compound is added as a countermeasure against the above-mentioned static electricity, a problem may occur in that the metal wiring is corroded by the ionic compound. Among the types of corrosion, pitting corrosion is particularly problematic when the metal layer is thin or when the metal layer is a metal wiring and has a narrow line width, because the metal layer is penetrated.
[0007] When the pressure-sensitive adhesives disclosed in the above Patent Documents 1 and 2 are used, antistatic properties are exhibited, but the performance is not necessarily sufficient, and the metal corrosion prevention properties are also not necessarily sufficient.
[0008] Therefore, an object of the present invention is to provide a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, and a polarizing plate with a pressure-sensitive adhesive, which have good adhesive strength, antistatic properties, and metal corrosion prevention properties. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides the following pressure-sensitive adhesive composition, pressure-sensitive adhesive layer, and pressure-sensitive adhesive-attached polarizing plate. [1] A pressure-sensitive adhesive composition comprising a (meth)acrylic resin (A-1) and an ionic compound (A-2), wherein the (meth)acrylic resin (A-1) contains structural units derived from an alkoxyalkyl (meth)acrylate in an amount of 10 mass% to 40 mass% based on the total amount of structural units constituting the (meth)acrylic resin (A-1), and the ionic compound (A-2) is an ionic compound comprising an anion moiety represented by the following formula (A-2-1) and an organic cation: [ka] [In the formula, R 4 and R 5 each independently represents a perfluoroalkyl group having 1 to 4 carbon atoms, or R 4 and R 5 represents a perfluoroalkylene group having 1 to 8 carbon atoms formed by bonding with [2] The pressure-sensitive adhesive composition according to the above-mentioned [1], wherein the structural unit derived from the alkoxyalkyl (meth)acrylate includes a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-1): [ka] [In the formula, R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkylene group having 1 to 4 carbon atoms, R 3 represents an alkyl group having 1 to 4 carbon atoms. [3] The pressure-sensitive adhesive composition according to the above-mentioned [1] or [2], wherein the (meth)acrylic resin (A-1) contains structural units derived from a carboxyl group-containing monomer in an amount of 0.6 mass% to 10 mass% based on the total amount of structural units constituting the (meth)acrylic resin (A-1). [4] The pressure-sensitive adhesive composition according to any one of the above [1] to [3], wherein the (meth)acrylic resin (A-1) contains a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-2): [ka] [In the formula, R 6 represents a hydrogen atom or a methyl group, R 7 represents an alkyl group or an aralkyl group having 1 to 14 carbon atoms.] [5] The (meth)acrylic resin (A-1) is represented by the above formula (A-1-2) and the above R 7 is an alkyl group having 1 to 3 carbon atoms, based on the total amount of structural units constituting the (meth)acrylic resin (A-1). [6] The pressure-sensitive adhesive composition according to any one of the above [1] to [5], wherein the content of the ionic compound (A-2) is from 0.1 to 10 parts by mass per 100 parts by mass of the (meth)acrylic resin (A-1). [7] The pressure-sensitive adhesive composition according to any one of the above [1] to [6], wherein the ionic compound (A-2) has a melting point of 23° C. or higher. [8] R of the anion part of the ionic compound (A-2) 4 and R 5 The pressure-sensitive adhesive composition according to any one of the above [1] to [7], wherein each of [9] The pressure-sensitive adhesive composition according to any one of the above [1] to [8], wherein the organic cation of the ionic compound (A-2) contains a nitrogen atom.
[10] A pressure-sensitive adhesive layer formed using the pressure-sensitive adhesive composition according to any one of the above [1] to [9].
[11] The pressure-sensitive adhesive layer according to the above
[10] , having a thickness of 2 μm or more and 50 μm or less.
[12] A polarizing plate with adhesive, comprising the adhesive layer according to
[10] or
[11] above and a polarizing plate attached thereto.
[13] The pressure-sensitive adhesive polarizing plate according to
[12] above, wherein the polarizing plate includes a retarder. Effect of the Invention
[0010] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, and a polarizing plate with a pressure-sensitive adhesive, which have good adhesive strength, antistatic properties, and metal corrosion prevention properties. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the optical laminate according to the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing another example of the optical laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings where necessary.
[0013] <Adhesive composition> The pressure-sensitive adhesive composition of the present invention contains a (meth)acrylic resin (A-1) and an ionic compound (A-2). The (meth)acrylic resin (A-1) contains 10% by mass or more and 40% by mass or less of structural units derived from alkoxyalkyl (meth)acrylate, based on the total amount of structural units constituting the (meth)acrylic resin (A-1). The ionic compound (A-2) is an ionic compound consisting of an anion moiety represented by the following formula (A-2-1) and an organic cation. [ka] In formula (A-2-1), R 4 and R 5 each independently represents a perfluoroalkyl group having 1 to 4 carbon atoms, or R 4 and R 5 represents a perfluoroalkylene group having 1 to 8 carbon atoms formed by bonding with
[0014] According to the pressure-sensitive adhesive composition, by using the specific ionic compound (A-2), good antistatic properties can be obtained, and metal corrosion prevention properties can be improved compared to the case of using other ionic compounds. Furthermore, according to the pressure-sensitive adhesive composition, by using the specific (meth)acrylic resin (A-1), metal corrosion prevention properties can be improved, and the ionic conductivity of the pressure-sensitive adhesive composition can be improved, so that the effect of improving antistatic properties by the ionic compound (A-2) can be enhanced. Furthermore, according to the pressure-sensitive adhesive composition, good adhesive strength can be obtained.
[0015] [(Meth)acrylic resin (A-1)] The (meth)acrylic resin (A-1) contains a structural unit derived from an alkoxyalkyl (meth)acrylate. The structural unit derived from an alkoxyalkyl (meth)acrylate may contain, for example, a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-1). The (meth)acrylic resin (A-1) may further contain at least one of a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-2), a structural unit derived from a carboxyl group-containing monomer, and a structural unit derived from a monomer having a polar functional group other than a carboxyl group. Here, (meth)acrylic acid means either acrylic acid or methacrylic acid, and the "(meth)" in (meth)acrylate and the like has the same meaning. [ka] In formula (A-1-1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkylene group having 1 to 4 carbon atoms, R 3 represents an alkyl group having 1 to 4 carbon atoms. [ka] In formula (A-1-2), R 6 represents a hydrogen atom or a methyl group, R 7represents an alkyl group or an aralkyl group having 1 to 14 carbon atoms.
[0016] Among the alkoxyalkyl (meth)acrylates, specific examples of the (meth)acrylic acid esters represented by the above formula (A-1-1) include 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-methoxy-2-ethoxyethyl acrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, and 2-methoxy-2-ethoxyethyl methacrylate. These (meth)acrylic acid esters can be used alone or copolymerized with different ones. Among these, it is preferable to use 2-methoxyethyl acrylate as one of the (meth)acrylic acid esters constituting the (meth)acrylic resin (A-1).
[0017] In the (meth)acrylic resin (A-1), the content of the structural unit derived from alkoxyalkyl (meth)acrylate is 10% by mass or more and 40% by mass or less based on the total amount of the structural units constituting the (meth)acrylic resin (A-1), but is preferably 15% by mass or more and 40% by mass or less, more preferably 15% by mass or more and 35% by mass or less, and particularly preferably 20% by mass or more and 35% by mass or less. If this content is less than 10% by mass, the ionic conductivity of the adhesive is low, so a large amount of antistatic agent needs to be added to ensure the desired antistatic properties, and the metal corrosion resistance is reduced, and if it exceeds 40% by mass, the polarity of the adhesive becomes high, which increases the moisture content and affects the adhesive properties.
[0018] The alkoxyalkyl (meth)acrylate is a (meth)acrylic acid ester other than the (meth)acrylic acid ester represented by the above formula (A-1-1) (for example, R 2 is other than an alkylene group having 1 to 4 carbon atoms, or R 3is other than an alkyl group having 1 to 4 carbon atoms) may or may not be contained. All of the structural units derived from an alkoxyalkyl(meth)acrylate may be structural units derived from a (meth)acrylic acid ester represented by the above formula (A-1-1).
[0019] Among the (meth)acrylic acid esters represented by the above formula (A-1-2), R 7 Specific examples of alkyl groups include linear alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, n-octyl acrylate, and lauryl acrylate; branched alkyl acrylates such as isobutyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate; linear alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, n-octyl methacrylate, and lauryl methacrylate; and branched alkyl methacrylates such as isobutyl methacrylate, 2-ethylhexyl methacrylate, and isooctyl methacrylate. 7 Specific examples of the (meth)acrylic acid ester represented by formula (A-1-2) in which is an aralkyl group include benzyl acrylate, benzyl methacrylate, etc. These (meth)acrylic acid esters can be used alone or copolymerized with different ones.
[0020] Among these, R 7 is an alkyl group having 1 to 3 carbon atoms, and a (meth)acrylic acid ester represented by formula (A-1-2) is preferably used as a copolymerization component. 7 is an alkyl group having 1 to 3 carbon atoms, and 7 It is more preferable to use in combination with (meth)acrylic acid represented by formula (A-1-2) in which is an alkyl group having 4 to 14 carbon atoms.
[0021] In the (meth)acrylic resin (A-1), the content of the structural unit derived from the (meth)acrylic acid ester represented by the above formula (A-1-2) is preferably 50% by mass or more and 89.4% by mass or less, more preferably 50% by mass or more and 84.4% by mass or less, even more preferably 55% by mass or more and 84.4% by mass or less, and particularly preferably 55% by mass or more and 79.4% by mass or less, based on the total amount of the structural units constituting the (meth)acrylic resin (A-1). When this content is 50% by mass or more and 89.4% by mass or less, the adhesive strength and durability can be appropriately adjusted.
[0022] In the (meth)acrylic resin (A-1), R 7 is an alkyl group having 1 to 3 carbon atoms, the content of structural units derived from a (meth)acrylic acid ester represented by formula (A-1-2) is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less, even more preferably 15% by mass or more and 35% by mass or less, and particularly preferably 20% by mass or more and 35% by mass or less, based on the total amount of structural units constituting the (meth)acrylic resin (A-1). When this content is 5% by mass or more and 50% by mass or less, durability can be appropriately ensured.
[0023] In the (meth)acrylic resin (A-1), R 7 When is an alkyl group having 4 to 14 carbon atoms, the content of structural units derived from a (meth)acrylic acid ester represented by formula (A-1-2) is preferably 0% by mass or more and 84.4% by mass or less, more preferably 10% by mass or more and 79.4% by mass or less, even more preferably 15% by mass or more and 74.4% by mass or less, and particularly preferably 15% by mass or more and 69.4% by mass or less, based on the total amount of structural units constituting the (meth)acrylic resin (A-1). When this content is 0% by mass or more and 84.4% by mass or less, the tackiness and durability of the pressure-sensitive adhesive can be appropriately adjusted.
[0024] The (meth)acrylic resin (A-1) preferably contains a structural unit derived from a carboxyl group-containing monomer. In the (meth)acrylic resin (A-1), the content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.6% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 5% by mass or less, and even more preferably 1% by mass or more and 3% by mass or less, based on the total amount of the structural units constituting the (meth)acrylic resin (A-1). When the content is 0.6% by mass or more, the adhesive strength and durability are improved by improving the glass adhesion, and when the content is 10% by mass or less, the excessive presence of the acid component can be suppressed, so that the decrease in the metal corrosion prevention property can be suppressed, and furthermore, the polarity of the adhesive can be suppressed from increasing, so that the moisture content can be suppressed from increasing and affecting the adhesive properties.
[0025] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, maleic acid, maleic anhydride, fumaric acid, crotonic acid, and carboxyalkyl (meth)acrylates (e.g., carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate). The carboxyl group-containing monomer may be a monomer having a free carboxyl group, such as β-carboxyethyl acrylate. Among these, it is preferable to use (meth)acrylic acid from the viewpoint of improving durability.
[0026] Examples of monomers having a polar functional group other than a carboxyl group include monomers having a polar functional group such as a hydroxyl group, an amino group, or a heterocyclic group including an epoxy ring, and preferably include (meth)acrylic acid-based compounds having a polar functional group.
[0027] Examples of monomers having a polar functional group include monomers having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2- or 3-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, and 2-hydroxybutyl (meth)acrylate; monomers having a heterocyclic group such as acryloylmorpholine, vinylcaprolactam, N-vinyl-2-pyrrolidone, tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, glycidyl (meth)acrylate, and 2,5-dihydrofuran; and monomers having an amino group different from the heterocyclic ring such as N,N-dimethylaminoethyl (meth)acrylate. These monomers having a polar functional group may be used alone or in combination.
[0028] The polar functional group of the monomer having a polar functional group is preferably a hydroxyl group, an amino group, or an epoxy ring. In particular, it is preferable to use a monomer having a hydroxyl group as one of the monomers constituting the (meth)acrylic resin (A-1). In addition to the monomer having a hydroxyl group, it is also effective to use a monomer having another polar functional group in combination.
[0029] In the (meth)acrylic resin (A-1), the content of structural units derived from a monomer having a polar functional group other than a carboxyl group is preferably 0.5% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 5% by mass or less, even more preferably 0.5% by mass or more and 3% by mass or less, and particularly preferably 1.0% by mass or more and 3% by mass or less, based on the total amount of structural units constituting the (meth)acrylic resin (A-1). If the content is 0.5% by mass or more, the number of reaction sites with the crosslinking agent described below increases, and durability can be improved, and if it is 10% by mass or less, the polarity of the adhesive can be prevented from increasing, and the moisture content can be prevented from increasing and affecting the adhesive properties.
[0030] The (meth)acrylic resin (A-1) may contain a structural unit derived from a monomer other than those mentioned above. Examples of the structural unit derived from another monomer include a structural unit derived from a (meth)acrylic acid ester having an alicyclic structure in the molecule, a structural unit derived from a styrene monomer, a structural unit derived from a vinyl monomer, and a structural unit derived from a monomer having a plurality of (meth)acryloyl groups in the molecule.
[0031] The alicyclic structure is a cycloparaffin structure having a carbon number of usually 5 or more, preferably about 5 to 7. Specific examples of acrylic acid esters having an alicyclic structure include isobornyl acrylate, cyclohexyl acrylate, dicyclopentanyl acrylate, cyclododecyl acrylate, methylcyclohexyl acrylate, trimethylcyclohexyl acrylate, tert-butylcyclohexyl acrylate, α-ethoxycyclohexyl acrylate, and cyclohexylphenyl acrylate. Specific examples of methacrylic acid esters having an alicyclic structure include isobornyl methacrylate, cyclohexyl methacrylate, dicyclopentanyl methacrylate, cyclododecyl methacrylate, methylcyclohexyl methacrylate, trimethylcyclohexyl methacrylate, tert-butylcyclohexyl methacrylate, and cyclohexylphenyl methacrylate.
[0032] Examples of styrene-based monomers include, in addition to styrene, alkyl styrenes such as methylstyrene, dimethylstyrene, trimethylstyrene, ethylstyrene, diethylstyrene, triethylstyrene, propylstyrene, butylstyrene, hexylstyrene, heptylstyrene, and octylstyrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; and further, nitrostyrene, acetylstyrene, methoxystyrene, and divinylbenzene.
[0033] Examples of vinyl monomers include fatty acid vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, and vinyl laurate; vinyl halides such as vinyl chloride and vinyl bromide; vinylidene halides such as vinylidene chloride; nitrogen-containing aromatic vinyls such as vinylpyridine, vinylpyrrolidone, and vinylcarbazole; conjugated diene monomers such as butadiene, isoprene, and chloroprene; and further, acrylonitrile, methacrylonitrile, and the like.
[0034] Examples of monomers having multiple (meth)acryloyl groups in the molecule include monomers having two (meth)acryloyl groups in the molecule, such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; and monomers having three (meth)acryloyl groups in the molecule, such as trimethylolpropane tri(meth)acrylate.
[0035] The other monomers as described above can be used alone or in combination of two or more. In the (meth)acrylic resin (A-1), the content of the structural units derived from the other monomers may be 0% by mass or more and 20% by mass or less, or 0% by mass or more and 10% by mass or less, based on the total amount of the structural units constituting the (meth)acrylic resin (A-1).
[0036] The adhesive composition may contain one type of (meth)acrylic resin (A-1) alone or two or more types. Furthermore, the adhesive composition may contain other (meth)acrylic resins that do not fall under the category of (meth)acrylic resin (A-1). When the adhesive composition contains other (meth)acrylic resins, the content of the (meth)acrylic resin (A-1) is preferably 60% by mass or more, more preferably 80% by mass or more, of the total (meth)acrylic resins.
[0037] The (meth)acrylic resin (A-1) preferably has a weight average molecular weight (Mw) in the range of 1 to 2 million as calculated using standard polystyrene by gel permeation chromatography (GPC). If the weight average molecular weight is 1 million or more as calculated using standard polystyrene, the adhesiveness at high temperature and high humidity is improved, and the possibility of lifting or peeling between the metal layer or glass substrate and the adhesive layer tends to be low, which is preferable. In addition, if the weight average molecular weight is 2 million or less, the viscosity of the adhesive solution adjusted during the preparation of the adhesive layer is in an appropriate range, and streaks and unevenness during preparation can be suppressed.
[0038] The (meth)acrylic resin (A-1) preferably has a glass transition temperature in the range of −10 to −60° C., more preferably in the range of −20 to −50° C., and even more preferably in the range of −30 to −45° C. The glass transition temperature of a resin can generally be measured by a differential scanning calorimeter.
[0039] The (meth)acrylic resin (A-1) may be composed of only the above-mentioned relatively high molecular weight resin, or may be composed of a mixture of the above-mentioned (meth)acrylic resin (A-1) and a (meth)acrylic resin (A-1) having a different molecular weight. Examples of the (meth)acrylic resin (A-1) that can be used in a mixture include (meth)acrylic resin (A-1) having a weight average molecular weight in the range of 50,000 to 300,000.
[0040] The (meth)acrylic resin (A-1) (a mixture of both when two or more types are combined) is dissolved in ethyl acetate and adjusted to a non-volatile concentration of 20% by mass, and the solution preferably exhibits a viscosity of 20 Pa·s or less, more preferably 0.1 to 15 Pa·s, at 25°C. If the viscosity is 20 Pa·s or less, it is possible to suppress the occurrence of streaks during the preparation of the adhesive, which is preferable. The viscosity can be measured using a Brookfield viscometer.
[0041] The (meth)acrylic resin (A-1) can be produced by various known methods, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization. In the production of this (meth)acrylic resin (A-1), a polymerization initiator is usually used. The polymerization initiator is used in an amount of about 0.001 to 5 parts by mass relative to 100 parts by mass of the total of all monomers used in the production of the (meth)acrylic resin (A-1).
[0042] As the polymerization initiator, a thermal polymerization initiator or a photopolymerization initiator is used. As the photopolymerization initiator, for example, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone can be mentioned. As the thermal polymerization initiator, for example, azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-hydroxymethylpropionitrile); lauryl peroxide; Examples of the peroxide include organic peroxides such as diisopropyl peroxydicarbonate, dipropyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, and (3,5,5-trimethylhexanoyl)peroxide; and inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide. Redox initiators using a combination of a peroxide and a reducing agent can also be used as the polymerization initiator.
[0043] Among the above-mentioned methods, the solution polymerization method is preferred as a method for producing the (meth)acrylic resin (A-1). A specific example of the solution polymerization method is a method in which a desired monomer and an organic solvent are mixed, a thermal polymerization initiator is added under a nitrogen atmosphere, and the mixture is stirred for about 3 to 10 hours at about 40 to 90°C, preferably about 60 to 80°C. In order to control the reaction, the monomer and the thermal polymerization initiator may be added continuously or intermittently during polymerization, or may be added in a state dissolved in an organic solvent. Examples of the organic solvent that can be used herein include aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; aliphatic alcohols such as propyl alcohol and isopropyl alcohol; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.
[0044] [Ionic compound (A-2)] The pressure-sensitive adhesive composition contains an ionic compound (A-2) as an antistatic agent in addition to the (meth)acrylic resin (A-1). The ionic compound (A-2) is composed of an anion moiety represented by the above formula (A-2-1) and an organic cation. The ionic compound (A-2) may be solid at room temperature (25°C).
[0045] Examples of the organic cation constituting the ionic compound (A-2) include imidazolium cation, pyridinium cation, pyrrolidinium cation, ammonium cation, sulfonium cation, phosphonium cation, etc. Among these, organic cations containing nitrogen atoms are preferred, and from the viewpoint of suppressing the refractive index fluctuation of the adhesive due to the use of an aromatic ring-containing compound, aliphatic cations are more preferred, and pyrrolidinium cation and ammonium cation are even more preferred.
[0046] Specific examples of organic cations include ammonium cations such as tributylmethylammonium cation, trioctylmethylammonium cation, trimethylpropylammonium cation, tetrabutylammonium cation, and (2-hydroxyethyl)trimethylammonium cation; phosphonium cations such as tributyldodecylphosphonium cation; pyridinium cations such as 1-hexylpyridinium cation, 1-octylpyridinium cation, 4-methyl-1-hexylpyridinium cation, 4-methyl-1-octylpyridinium cation, and 4-methyl-1-butylpyridinium cation; pyrrolidinium cations such as butylmethylpyrrolidinium cation and ethylmethylpyrrolidinium cation; and imidazolium cations such as 1-ethyl-3-methylimidazolium cation and 1-butyl-3-methylimidazolium cation.
[0047] The anion constituting the ionic compound (A-2) is an anion represented by the above formula (A-2-1). Among these, from the viewpoint of ease of exhibiting antistatic performance at the same addition weight, R 4 and R 5 is preferably a trifluoromethyl anion.
[0048] Specific examples of the anion represented by the above formula (A-2-1) include bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - 〕, bis(pentafluoroethanesulfonyl)imide anion [(C2F5SO2)2N - ], bis(heptafluoropropanesulfonyl)imide anion, bis(nonafluorobutanesulfonyl)imide anion, trifluoromethanesulfonyl(pentafluoroethanesulfonyl)imide anion, trifluoromethanesulfonyl(heptafluoropropanesulfonyl)imide anion, trifluoromethanesulfonyl(nonafluorobutanesulfonyl)imide anion, 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonimide anion, and the like.
[0049] The ionic compound (A-2) may be used alone or in combination of two or more. The pressure-sensitive adhesive composition may contain an ionic compound other than the ionic compound (A-2).
[0050] As described above, the ionic compound (A-2) is effective in imparting antistatic properties to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition containing the (meth)acrylic resin (A-1) and in maintaining various physical properties as a pressure-sensitive adhesive. In particular, when an ionic compound (A-2) that is solid at room temperature is used, the antistatic performance can be maintained for a long period of time compared to when an ionic compound that is liquid at room temperature is used. From the viewpoint of long-term stability of antistatic properties, the ionic compound (A-2) preferably has a melting point of 23°C or higher. On the other hand, if the melting point is too high, the compatibility with the (meth)acrylic resin (A-1) becomes poor, so it is preferable that the ionic compound (A-2) has a melting point of 90°C or lower, further 80°C or lower, and particularly 50°C or lower. The molecular weight of the ionic compound (A-2) is not particularly limited, but for example, the molecular weight is preferably 700 or lower, further preferably 500 or lower.
[0051] The content of the ionic compound (A-2) in the pressure-sensitive adhesive composition is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.1 parts by mass or more and 5 parts by mass or less, even more preferably 0.1 parts by mass or more and 2.5 parts by mass or less, and particularly preferably 0.1 parts by mass or more and 1.5 parts by mass or less, relative to 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1). When the ionic compound (A-2) is contained in an amount of 0.1 parts by mass or more relative to 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1), the antistatic performance is improved, and when the amount is 10 parts by mass or less, the bleeding out of the ionic compound from the pressure-sensitive adhesive layer during a durability test can be suppressed, and durability can be easily maintained, which is preferable.
[0052] [Crosslinking agent] The pressure-sensitive adhesive composition may further contain a crosslinking agent. The crosslinking agent is a compound having at least two functional groups in the molecule capable of crosslinking with a structural unit derived from, for example, a monomer having a polar functional group in the (meth)acrylic resin (A-1), and specific examples thereof include an isocyanate compound, an epoxy compound, a metal chelate compound, and an aziridine compound.
[0053] The isocyanate compound is a compound having at least two isocyanato groups (-NCO) in the molecule, and examples thereof include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, and dimers, trimers, etc. of isocyanate compounds can also be crosslinking agents used in adhesives. Two or more types of isocyanate compounds can also be used in combination.
[0054] The epoxy compound is a compound having at least two epoxy groups in the molecule, and examples thereof include bisphenol A type epoxy resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N-diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, etc. Two or more kinds of epoxy compounds can also be used in combination.
[0055] Examples of the metal chelate compound include compounds in which acetylacetone or ethyl acetoacetate is coordinated with a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, or zirconium.
[0056] An aziridine compound is a compound having at least two three-membered ring skeletons consisting of one nitrogen atom and two carbon atoms, also known as ethyleneimine, in the molecule. Examples of such compounds include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, isophthaloylbis-1-(2-methylaziridine), tris-1-aziridinylphosphine oxide, hexamethylene-1,6-bis(1-aziridinecarboxamide), trimethylolpropane-tri-β-aziridinylpropionate, and tetramethylolmethane-tri-β-aziridinylpropionate.
[0057] Among these crosslinking agents, isocyanate compounds, particularly xylylene diisocyanate, tolylene diisocyanate, or hexamethylene diisocyanate, or adducts obtained by reacting these isocyanate compounds with polyols such as glycerol or trimethylolpropane, dimers, trimers, etc. of isocyanate compounds, mixtures of these isocyanate compounds, etc. are preferably used. In particular, when the polar functional group-containing monomer has a polar functional group selected from a free carboxyl group, a hydroxyl group, an amino group, and an epoxy ring, it is preferable to use an isocyanate compound as at least one of the crosslinking agents. Suitable isocyanate compounds include tolylene diisocyanate, an adduct obtained by reacting tolylene diisocyanate with a polyol, a dimer of tolylene diisocyanate, and a trimer of tolylene diisocyanate, as well as hexamethylene diisocyanate, an adduct obtained by reacting hexamethylene diisocyanate with a polyol, a dimer of hexamethylene diisocyanate, and a trimer of hexamethylene diisocyanate.
[0058] The crosslinking agent is blended in an amount of 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and particularly preferably 0.1 to 1 part by mass, per 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1). When the amount of the crosslinking agent per 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1) is 0.01 parts by mass or more, the fluidity of the adhesive can be prevented from becoming too high, and the amount of deformation during a durability test can be prevented from becoming large, and when the amount is 10 parts by mass or less, the adhesive can be prevented from becoming too hard, and the occurrence of defects such as breakage of the adhesive during a durability test can be easily prevented.
[0059] [Other components constituting the adhesive composition] In the pressure-sensitive adhesive composition for forming the pressure-sensitive adhesive layer in the present invention, a silane-based compound is preferably contained in order to improve adhesion between the pressure-sensitive adhesive layer and a metal layer or a glass substrate, and in particular, it is preferable to contain a silane-based compound in the acrylic resin before blending with the crosslinking agent.
[0060] Examples of silane compounds include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, and 3-glycidoxypropylethoxydimethylsilane. Two or more silane compounds may be used.
[0061] The silane-based compound may be a silicone oligomer type. When the silicone oligomer is expressed in the form of a copolymer, for example, the following can be mentioned. That is, copolymers containing mercaptopropyl groups such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; copolymers containing mercaptomethyl groups such as mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, mercaptomethyltriethoxysilane-tetraethoxysilane copolymer; copolymers containing 3-methacryloyloxypropyltrimethoxysilane; methacryloyloxypropyl group-containing copolymers such as methacryloyloxypropyl group-containing copolymers, ...3-Acryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, copolymers containing acryloyloxypropyl groups, such as vinyltrimethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer; vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyl group-containing copolymers such as vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, vinylmethyldiethoxysilane-tetraethoxysilane copolymer; amino group-containing copolymers such as 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer;
[0062] From the viewpoint of the covering ability of the metal surface, the molecular weight of these silane compounds is preferably 1000 or less, more preferably 500 or less, and particularly preferably 250 or less. From the viewpoint of the bond between the silane compound and the pressure-sensitive adhesive composition, the silane compound preferably contains an epoxy group.
[0063] These silane compounds are often liquid. The amount of the silane compound in the pressure-sensitive adhesive composition is usually about 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1) (total mass when two or more types are used). When the amount of the silane compound is 0.01 parts by mass or more relative to 100 parts by mass of the nonvolatile content of the (meth)acrylic resin (A-1), the adhesion between the pressure-sensitive adhesive layer and the metal layer or glass substrate is improved, which is preferable. In addition, when the amount is 10 parts by mass or less, the bleeding out of the silane compound from the pressure-sensitive adhesive layer tends to be suppressed, which is preferable.
[0064] The adhesive composition described above may further contain a crosslinking catalyst, a weathering stabilizer, a tackifier, a plasticizer, a softener, a dye, a pigment, an inorganic filler, a resin other than the (meth)acrylic resin (A-1), and the like. It is also useful to add an ultraviolet-curable compound to the adhesive composition, and to cure the adhesive layer by irradiating it with ultraviolet light after the adhesive layer is formed, to obtain a harder adhesive layer. In particular, if a crosslinking catalyst is added to the adhesive composition together with a crosslinking agent, the adhesive layer can be prepared in a short period of aging, and the resulting adhesive-attached resin film can be prevented from floating or peeling between the resin film and the adhesive layer, or from foaming within the adhesive layer. Examples of the crosslinking catalyst include amine compounds such as hexamethylenediamine, ethylenediamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethylenetetramine, isophoronediamine, trimethylenediamine, polyamino resin, and melamine resin. When an amine compound is blended as a crosslinking catalyst in the pressure-sensitive adhesive composition, an isocyanate compound is preferable as the crosslinking agent.
[0065] Each of these components constituting the pressure-sensitive adhesive composition is dissolved in a solvent and applied onto a suitable substrate, followed by drying to form a pressure-sensitive adhesive layer.
[0066] <Optical film with adhesive> The optical film with adhesive of the present invention is an optical film having an adhesive layer formed from the above-mentioned adhesive composition on at least one side thereof. The optical film used here is a film having optical properties, such as a polarizing plate (linear polarizing plate or circular polarizing plate). The polarizing plate may include a retardation film. That is, the optical film with adhesive may be a polarizing plate with adhesive.
[0067] (Optical film) Examples of optical films include a linear polarizing layer; a linear polarizing plate having a protective layer on one or both sides of a linear polarizing layer; a circular polarizing plate including a linear polarizing layer or a linear polarizing plate and one or more retarders; a polarizing plate with a surface protective film in which a surface protective film is provided on one side of a polarizing plate such as a linear polarizing plate or a circular polarizing plate; a retarder; a retardation plate having a protective layer on one or both sides of a retarder; a reflective film; a semi-transmissive reflective film; a brightness improving film; and a film with an anti-glare function, and one or more of these may be used in combination. The optical film preferably includes at least a linear polarizing layer, and more preferably includes a linear polarizing plate or a circular polarizing plate. The retarder included in the circular polarizing plate includes at least one retardation film, and at least one of them is usually a λ / 4 retardation film.
[0068] (Linear polarizing layer) The linearly polarizing layer has a property of transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis when non-polarized light is incident. The linearly polarizing layer may be a polyvinyl alcohol-based resin film (hereinafter, sometimes referred to as a "PVA-based film") in which iodine is adsorbed and aligned, or may be a film including a liquid crystal polarizing layer formed by applying a composition including a compound having absorption anisotropy and liquid crystallinity to a substrate film. The compound having absorption anisotropy and liquid crystallinity may be a mixture of a dye having absorption anisotropy and a compound having liquid crystallinity, or may be a dye having absorption anisotropy and liquid crystallinity.
[0069] The linear polarizing layer, which is a PVA-based film, may be, for example, a PVA-based film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, or an ethylene-vinyl acetate copolymer-based partially saponified film, which has been dyed with iodine and stretched. If necessary, the PVA-based film in which iodine has been adsorbed and oriented by the dyeing process may be treated with an aqueous boric acid solution, and then a washing process may be performed to wash off the aqueous boric acid solution. A known method may be used for each step.
[0070] Polyvinyl alcohol resins (hereinafter sometimes referred to as "PVA resins") can be produced by saponifying polyvinyl acetate resins. Polyvinyl acetate resins can be polyvinyl acetate, which is a homopolymer of vinyl acetate, or a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0071] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually about 1,000 to 10,000, preferably about 1,500 to 5,000. The saponification degree and average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726 (1994). If the average polymerization degree is less than 1,000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10,000, the film processability may be poor.
[0072] The method for producing the linearly polarizing layer, which is a PVA-based film, may include the steps of preparing a substrate film, applying a solution of a resin such as a PVA-based resin onto the substrate film, and performing drying to remove the solvent to form a resin layer on the substrate film. A primer layer may be formed in advance on the surface of the substrate film on which the resin layer is to be formed. As the substrate film, a film using a resin material described as a thermoplastic resin used to form a protective film as a protective layer, which will be described later, may be used. As the material for the primer layer, a resin obtained by crosslinking a hydrophilic resin used in the linearly polarizing layer may be mentioned.
[0073] Next, the amount of solvent such as water in the resin layer is adjusted as necessary, and then the base film and the resin layer are uniaxially stretched, and then the resin layer is dyed with iodine to adsorb and align iodine in the resin layer. Next, if necessary, the resin layer with iodine adsorbed and oriented is treated with an aqueous boric acid solution, and then a washing step is performed to wash off the aqueous boric acid solution. This produces a resin layer with iodine adsorbed and oriented, that is, a PVA-based film that becomes a linearly polarizing layer. A known method can be used for each step.
[0074] The amount of boric acid in the boric acid-containing aqueous solution for treating the PVA-based film or resin layer in which iodine is adsorbed and oriented is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. This boric acid-containing aqueous solution preferably contains potassium iodide. The amount of potassium iodide in the boric acid-containing aqueous solution is usually about 0.1 to 15 parts by mass, preferably about 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the boric acid-containing aqueous solution is usually about 60 to 1,200 seconds, preferably about 150 to 600 seconds, more preferably about 200 to 400 seconds. The temperature of the boric acid-containing aqueous solution is usually 50°C or higher, preferably 50 to 85°C, more preferably 60 to 80°C.
[0075] The uniaxial stretching of the PVA-based film, the substrate film, and the resin layer may be performed before dyeing, during dyeing, or during boric acid treatment after dyeing, and uniaxial stretching may be performed at each of these multiple stages. The PVA-based film, the substrate film, and the resin layer may be uniaxially stretched in the MD direction (film transport direction). In this case, they may be uniaxially stretched between rolls with different peripheral speeds, or may be uniaxially stretched using a heated roll. The PVA-based film, the substrate film, and the resin layer may be uniaxially stretched in the TD direction (direction perpendicular to the film transport direction). In this case, a so-called tenter method can be used. The above stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state in which the PVA-based film or the resin layer is swollen with a solvent. In order to exhibit the performance of the linearly polarizing layer, the stretching ratio is 4 times or more, preferably 5 times or more, and particularly preferably 5.5 times or more. There is no particular upper limit to the stretching ratio, but it is preferably 8 times or less from the viewpoint of suppressing breakage and the like.
[0076] The linear polarizing layer produced by the manufacturing method using the substrate film can be obtained by laminating a protective layer and then peeling off the substrate film. This method makes it possible to further reduce the thickness of the linear polarizing layer.
[0077] The thickness of the linearly polarizing layer, which is a PVA-based film, is preferably 1 μm or more, may be 2 μm or more, or may be 5 μm or more, and is preferably 30 μm or less, more preferably 15 μm or less, may be 10 μm or less, or may be 8 μm or less. If the linearly polarizing layer is less than 1 μm thick, defects such as breakage may occur during the process, and if it exceeds 30 μm, the optical film becomes too thick, which is inappropriate.
[0078] The film including a liquid crystal linear polarizing layer may be a linear polarizing layer obtained by applying a composition including a dye having liquid crystallinity and absorption anisotropy, or a composition including a dye having absorption anisotropy and a polymerizable liquid crystal to a substrate film. The liquid crystal linear polarizing layer may be a cured product of a polymerizable liquid crystal compound, and may include an alignment film. The alignment film may be an alignment film included in a retardation film described later. The film including a liquid crystal linear polarizing layer may be a liquid crystal linear polarizing layer, and may have a laminated structure of a liquid crystal linear polarizing layer and a substrate film. The substrate film may be, for example, a film using a resin material described as a thermoplastic resin used to form a protective film as a protective layer described later. The film including a liquid crystal linear polarizing layer may be, for example, a polarizing layer described in JP-A-2013-33249.
[0079] The total thickness of the substrate film and the linear polarizing layer formed as described above is preferably small. However, if it is too small, the strength decreases and the processability tends to be poor, so it is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0080] (protective layer) Examples of the protective layer include a protective film formed from a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture blocking properties, isotropy, stretchability, etc., and an overcoat layer formed from a composition having excellent solvent resistance, transparency, mechanical strength, thermal stability, shielding properties, isotropy, etc. The protective film is preferably laminated on the linearly polarizing layer via an attachment layer, and the overcoat layer is preferably laminated so as to be in direct contact with the linearly polarizing layer.
[0081] Specific examples of thermoplastic resins for forming the protective film include cellulose resins such as triacetyl cellulose, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene resins), (meth)acrylic resins, polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The thickness of the protective film is preferably 3 μm or more, more preferably 5 μm or more, and is preferably 50 μm or less, more preferably 30 μm or less.
[0082] The overcoat layer can be formed from a composition having excellent solvent resistance, transparency, mechanical strength, thermal stability, shielding properties, isotropy, etc. The overcoat layer can be formed, for example, by applying the above-mentioned composition onto the linearly polarizing layer. Examples of materials constituting the overcoat layer include photocurable resins and water-soluble polymers, and (meth)acrylic resins, polyvinyl alcohol resins, polyamide epoxy resins, etc. can be used. The thickness of the overcoat layer can be, for example, 0.1 μm or more and 10 μm or less.
[0083] The protective layer may have anti-reflection properties, anti-glare properties, hard coat properties, etc. (Hereinafter, a protective film having such properties may be referred to as a "functional protective layer.") When the protective layer is not a functional protective layer, a surface functional layer such as an anti-reflection layer, an anti-glare layer, a hard coat layer, etc. may be provided on one side of the linear polarizing plate. The surface functional layer is preferably provided so as to be in direct contact with the protective layer. The surface functional layer is preferably provided on the side of the protective layer opposite to the linear polarizing layer side.
[0084] Although the above description has been given of the case where the protective layer is provided on the linear polarizing layer, the protective layer may be provided on the retardation film.
[0085] (phaser) A retarder is an optical element that exhibits a retardation in the in-plane or thickness direction, and includes at least one retardation film. The retardation film may be one, or two or more may be bonded together with a known adhesive or pressure-sensitive adhesive. Among them, it is preferable to use two retardation films in combination, since the retardation can be appropriately adjusted when used as a circular polarizing plate.
[0086] (phase contrast film) The retardation film is a film that exhibits retardation in the in-plane or thickness direction, and may be a stretched film or may include a layer of a cured product of a polymerizable liquid crystal compound.
[0087] When the retardation film is a stretched film, the stretched film may be a conventionally known one, and may be a resin film that is uniaxially or biaxially stretched to give a retardation. As the resin film, cellulose films such as triacetyl cellulose and diacetyl cellulose, polyester films such as polyethylene terephthalate, polyethylene isophthalate and polybutylene terephthalate, acrylic resin films such as polymethyl (meth) acrylate and polyethyl (meth) acrylate, polycarbonate films, polyethersulfone films, polysulfone films, polyimide films, polyolefin films, polynorbornene films, etc. may be used, but are not limited thereto.
[0088] When the retardation film includes the above-mentioned cured product layer, the polymerizable liquid crystal compound may be a known polymerizable liquid crystal compound. The polymerizable liquid crystal compound is a compound having at least one polymerizable group and having liquid crystal properties.
[0089] The polymerizable group of the polymerizable liquid crystal compound means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. The photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, a (meth)acryloyloxy group, an oxiranyl group, an oxetanyl group, a styryl group, and an allyl group. Among them, a (meth)acryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property of the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, and when the thermotropic liquid crystal is classified by the degree of order, it may be a nematic liquid crystal or a smectic liquid crystal. When two or more types of polymerizable liquid crystal compounds are used in combination to form a cured layer of the polymerizable liquid crystal compound, it is preferable that at least one type has two or more polymerizable groups in the molecule.
[0090] When the retardation film includes the cured product layer, the retardation film may include an alignment film. The alignment film has an alignment regulating force for aligning the polymerizable liquid crystal compound in a desired direction. The alignment film may be a vertical alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned vertically to the planar direction of the laminate, a horizontal alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned horizontally to the planar direction of the laminate, or an inclined alignment film in which the molecular axis of the polymerizable liquid crystal compound is aligned at an angle to the planar direction of the laminate.
[0091] The cured product layer can be formed by applying a composition for forming a retardation film containing a polymerizable liquid crystal compound, a solvent, and various additives as necessary, on an alignment film to form a coating film, and solidifying (curing) the coating film. Alternatively, the composition can be applied to a substrate film to form a coating film, and the coating film can be stretched together with the substrate film to form a cured product layer. The composition may contain a polymerization initiator, a reactive additive, a leveling agent, a polymerization inhibitor, and the like, in addition to the polymerizable liquid crystal compound and solvent described above. The polymerizable liquid crystal compound, the solvent, the polymerization initiator, the reactive additive, the leveling agent, the polymerization inhibitor, and the like can be appropriately used as known polymerizable liquid crystal compounds, solvents, polymerization initiators, reactive additives, leveling agents, polymerization inhibitors, and the like. As the substrate film, a film using a resin material described as the thermoplastic resin used to form the protective film as the protective layer can be used.
[0092] (Surface protection film) The surface protective film is provided releasably to the polarizing plate. The surface protective film may have a single-layer structure or a multi-layer structure. The surface protective film may include a base layer and a second adhesive layer, or may be a self-adhesive base layer.
[0093] The base layer constituting the surface protective film can be a film using the resin material described as the thermoplastic resin used to form the protective film as the protective layer. The adhesive composition for forming the second adhesive layer can be formed using a known adhesive composition. Examples of known adhesive compositions include those described above in the adhesive composition.
[0094] The surface protection film including the base layer and the second adhesive layer can be formed by applying the adhesive composition itself or an organic solvent dilution of the adhesive composition onto the base layer and drying it. Examples of the method for applying the adhesive composition or the organic solvent dilution thereof include a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, and a gravure coating method.
[0095] When the surface protection film has self-adhesive properties, examples of the thermoplastic resin constituting the self-adhesive base layer include polypropylene-based resins and polyethylene-based resins.
[0096] Although the above describes the case where the surface protective film is used for the polarizing plate, the surface protective film may be laminated on a member exemplified as an optical film other than the polarizing plate.
[0097] (Lamination layer) When the optical film has a multi-layer structure, the layers may be bonded together by a bonding layer. The bonding layer is a pressure-sensitive adhesive layer or an adhesive layer. When the bonding layer is a pressure-sensitive adhesive layer, it can be formed using a known pressure-sensitive adhesive composition. Examples of known pressure-sensitive adhesive compositions include those described above in the pressure-sensitive adhesive composition.
[0098] When the attachment layer is an adhesive layer, the adhesive layer can be formed by curing a curable component in an adhesive composition. The adhesive composition for forming the adhesive layer is an adhesive other than a pressure-sensitive adhesive (adhesive), and examples thereof include a water-based adhesive and an active energy ray curable adhesive.
[0099] Examples of the water-based adhesive include an adhesive in which a polyvinyl alcohol resin is dissolved or dispersed in water. The drying method when using a water-based adhesive is not particularly limited, but for example, a method of drying using a hot air dryer or an infrared dryer can be adopted.
[0100] Examples of the active energy ray curable adhesive include a solventless active energy ray curable adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays. By using a solventless active energy ray curable adhesive, the adhesion between layers can be improved.
[0101] (Optical film with adhesive) The optical film with adhesive is preferably attached with a release film on the surface of the adhesive layer, and the surface of the adhesive layer is protected until use. The optical film with adhesive provided with a release film in this way can be produced by, for example, a method of applying the above-mentioned adhesive composition on a release film to form an adhesive layer, and further laminating an optical film on the obtained adhesive layer, a method of applying the adhesive composition on an optical film to form an adhesive layer, and laminating a release film on the adhesive surface to protect it, a method of applying the above-mentioned adhesive composition on a release film to form an adhesive layer, and further laminating another release film on the obtained adhesive layer, and then peeling one of the release films, laminating an optical film on the exposed adhesive surface, and the like. In particular, the method of applying the above-mentioned adhesive composition on a release film to form an adhesive layer, and further laminating another release film on the obtained adhesive layer, and then peeling one of the release films, laminating an optical film on the exposed adhesive surface, and the like, is preferable from the viewpoint of stabilizing the physical properties during the curing period of the adhesive. In particular, the release film used here can be, for example, a film made of various resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyarylate, etc., used as a base material, and the bonding surface of this base material with the pressure-sensitive adhesive layer can be subjected to a release treatment such as silicone treatment.
[0102] The thickness of the adhesive layer is not particularly limited, but is usually preferably 2 μm to 50 μm, more preferably 5 μm to 30 μm, even more preferably 5 μm to 25 μm, and particularly preferably 10 μm to 20 μm. If the thickness of the adhesive layer is 2 μm or more, the adhesiveness can be prevented from decreasing, so that the possibility of a problem occurring in durability can be reduced, and if it is 50 μm or less, the problem of the end face of the adhesive sticking to the cutting blade and coming off when cutting the adhesive or the optical film with the adhesive can be prevented.
[0103] The pressure-sensitive adhesive optical film of the present invention has good adhesive strength, antistatic properties and metal corrosion prevention properties of the pressure-sensitive adhesive layer, and therefore can be suitably used in image display devices and the like.
[0104] <Optical laminate> FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate according to the present invention. As shown in FIG. 1, the optical laminate 100 according to the present invention includes an optical film 10, a pressure-sensitive adhesive layer 20, and a metal layer 30 in this order, and may further include a substrate 40. This optical laminate 100 can be obtained by laminating an optical film 1 with a pressure-sensitive adhesive, which includes an optical film 10 and a pressure-sensitive adhesive layer 20 laminated on at least one surface of the optical film 10, on a metal layer 30 formed on a substrate 40, via the pressure-sensitive adhesive layer 20. As the optical film 1 with a pressure-sensitive adhesive, the one described above can be used. The optical film 10 may be an optical film with a single layer structure or an optical film with a multilayer structure.
[0105] The adhesive layer 20 is usually laminated directly on the surface of the optical film 10. Also, usually, the optical film 1 with adhesive is laminated on the metal layer 30 so that the adhesive layer 20 is in direct contact with the metal layer 30. Also, when the resin layer 50 is provided on the metal layer 30 as described later, the adhesive layer 20 is laminated so that the adhesive layer 20 is in direct contact with the resin layer 50. According to the present invention, since the adhesive layer 20 is formed using the above-mentioned adhesive composition of the present invention, the corrosion of the metal layer 30 can be effectively suppressed in the optical laminate 100. Also, the adhesive layer 20 has good adhesion to the optical film 10, the metal layer 30, and the substrate 40, and has good antistatic properties. In this specification, the property of suppressing the corrosion of the metal layer 30 is also referred to as metal corrosion prevention property.
[0106] The metal layer 30 may be, for example, a layer containing one or more selected from the group consisting of aluminum, titanium, copper, silver, gold, iron, tin, zinc, nickel, molybdenum, chromium, tungsten, lead, and alloys containing two or more metals selected from these, and from the viewpoint of electrical conductivity, it is preferably a layer containing a metal element selected from the group consisting of aluminum, titanium, copper, silver, and gold, and from the viewpoint of electrical conductivity and cost, it is more preferably a layer containing an aluminum element, and further preferably a layer containing an aluminum element as a main component. "Containing as a main component" means that the metal component constituting the metal layer 30 is 30 mass% or more, and further 50 mass% or more of the total metal components.
[0107] The metal layer 30 may be, for example, a metal oxide layer such as ITO, but since the pressure-sensitive adhesive-attached optical film 1 according to the present invention has particularly good corrosion resistance against simple metals and alloys, it is preferable that the metal layer 30 contains a simple metal made of the above metal elements and / or an alloy containing two or more of the above metal elements. However, the optical laminate 100 may have, in addition to such a metal layer 30, a transparent electrode layer made of a metal oxide such as ITO.
[0108] The form (e.g., thickness, etc.) and preparation method of the metal layer 30 are not particularly limited, and it can be a metal foil, or may be formed by vacuum deposition, sputtering, ion plating, inkjet printing, or gravure printing. However, it is preferably a metal layer formed by sputtering, inkjet printing, or gravure printing, and more preferably a metal layer formed by sputtering. A metal layer formed by sputtering tends to have poorer corrosion resistance than a metal foil, but the optical laminate 100 has good metal corrosion prevention properties even against a metal layer formed by sputtering. The thickness of the metal layer 30 is usually 3 μm or less, preferably 1 μm or less, and more preferably 0.8 μm or less. The thickness of the metal layer 30 is usually 0.01 μm or more. Furthermore, when the metal layer 30 is a metal wiring layer, the line width of the metal wiring of the metal wiring layer is usually 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. The line width of the metal wiring is usually 0.01 μm or more, preferably 0.1 μm or more, and more preferably 0.5 μm or more. The optical laminate 100 exhibits good metal corrosion prevention properties even for such a thin metal layer 30 or a metal layer 30 made of fine metal wiring. In particular, even when the metal wiring has a thickness of 3 μm or less and a line width of 10 μm or less, or a thickness of 3 μm or less and a line width of 10 μm or less and is formed by a sputtering method, the corrosion, particularly pitting corrosion, can be suppressed.
[0109] The metal layer 30 can be, for example, a metal wiring layer (i.e., an electrode layer) of a touch input element of a touch input type image display device or a display element of an organic EL panel. In this case, the metal layer 30 is usually patterned into a predetermined shape. When the adhesive layer 20 is laminated on the patterned metal layer 30, the adhesive layer 20 may have a portion that is not in contact with the metal layer 30. The metal layer 30 may be a continuous film containing the above metal or alloy.
[0110] The metal layer 30 may have a single-layer structure or a multi-layer structure of two or more layers. An example of a metal layer having a multi-layer structure is a metal-containing layer (such as a metal mesh) having a three-layer structure represented by molybdenum / aluminum / molybdenum.
[0111] As shown in Fig. 1, a metal layer 30, for example a metal wiring layer, is usually formed on a substrate 40, and in this case, the optical laminate 100 includes this substrate 40. The metal layer 30 can be formed on the substrate 40 by, for example, sputtering. The substrate 40 can be a transparent substrate constituting an image display device included in a touch input element, or a display element of an organic EL panel. The metal layer 30 may be formed on the entire surface of the substrate 40, or may be formed on a part of it.
[0112] FIG. 2 is a schematic cross-sectional view showing another example of the layer structure of the optical laminate according to the present invention. In another embodiment, the optical laminate according to the present invention is an optical laminate 200 shown in FIG. 2, in which the pressure-sensitive adhesive layer 20 of the pressure-sensitive adhesive-attached optical film 1 is laminated on the metal layer 30 via the resin layer 50. The pressure-sensitive adhesive layer 20 is in direct contact with the resin layer 50. In such an optical laminate 200, the corrosion of the metal layer 30 can be effectively suppressed. The resin layer 50 disposed between the pressure-sensitive adhesive layer 20 and the metal layer 30 may be, for example, a cured product layer of a curable resin. A known curable resin can be used as the curable resin that can form the resin layer 50.
[0113] As described above, the metal layer 30 may be a metal wiring layer. An example of the case where the metal layer 30 is a metal wiring layer is shown in Fig. 3. In the optical laminate 300 shown in Fig. 3, the resin layer 50 may be omitted.
[0114] The optical laminate can be produced, for example, by bonding an adhesive-backed optical film 1, which includes an optical film 10 and an adhesive layer 20 laminated on at least one side of the optical film 10, onto a metal layer 30 formed on a substrate 40, via the adhesive layer 20.
[0115] As described above, the pressure-sensitive adhesive optical film 1 includes an optical film 10 and a pressure-sensitive adhesive layer 20 laminated on at least one surface of the optical film 10 (FIG. 1). The pressure-sensitive adhesive layer 20 may be laminated on both surfaces of the optical film 10. Usually, the pressure-sensitive adhesive layer 20 is laminated directly on the surface of the optical film 10. When providing the pressure-sensitive adhesive layer 20 on the surface of the optical film 10, it is preferable to form a primer layer on the bonding surface of the optical film 10 and / or the bonding surface of the pressure-sensitive adhesive layer 20, or to subject the surface to surface activation treatment such as plasma treatment or corona treatment, and it is more preferable to subject the surface to corona treatment.
[0116] A separate antistatic layer may be provided between the optical film 10 and the pressure-sensitive adhesive layer 20. However, since the pressure-sensitive adhesive layer 20 of the present invention can impart excellent antistatic properties by itself, it is preferable not to have an antistatic layer between the optical film 10 and the pressure-sensitive adhesive layer 20 in terms of reducing the thickness of the optical laminate and simplifying the laminate production process.
[0117] The pressure-sensitive adhesive optical film 1 may include a separate film (release film) laminated on the outer surface of the pressure-sensitive adhesive layer 20. This separate film is usually peeled off and removed when the pressure-sensitive adhesive layer 20 is used (for example, when laminated on the metal layer 30). The separate film may be, for example, a film made of various resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyarylate, etc., with a release treatment such as silicone treatment applied to the surface on which the pressure-sensitive adhesive layer 20 is formed.
[0118] The optical film 1 with a pressure-sensitive adhesive can be obtained by dissolving or dispersing each component constituting the pressure-sensitive adhesive composition in a solvent to form a solvent-containing pressure-sensitive adhesive composition, and then applying and drying this on the surface of the optical film 10 to form the pressure-sensitive adhesive layer 20. Alternatively, the optical film 1 with a pressure-sensitive adhesive can be obtained by forming the pressure-sensitive adhesive layer 20 on the release-treated surface of a separate film in the same manner as above, and laminating (transferring) this pressure-sensitive adhesive layer 20 onto the surface of the optical film 10.
[0119] An optical laminate can be obtained by laminating the optical film 1 with adhesive on the metal layer 30 (or the above-mentioned resin layer) via the adhesive layer 20. If any defect occurs after the optical laminate is produced by laminating the optical film 1 with adhesive and the metal layer 30, a so-called reworking operation may be required in which the optical film 1 with adhesive is peeled off from the metal layer 30 and another optical film 1 with adhesive is re-laid on the metal layer 30. The optical laminate according to the present invention is excellent in reworkability because fogging or adhesive residue is unlikely to occur on the surface of the metal layer 30 after the optical film 1 with adhesive is peeled off from the metal layer 30. The optical laminate according to the present invention can exhibit good reworkability even when the surface to which the adhesive layer 20 is laminated is not the metal layer 30 but a glass substrate or an ITO layer.
[0120] <Image display device> The image display device according to the present invention includes the optical laminate according to the present invention. The image display device according to the present invention can suppress corrosion of the metal layer 30 and also exhibits good durability. EXAMPLES
[0121] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" representing blend amounts or contents are based on mass unless otherwise specified.
[0122] In the following examples, the solid content (non-volatile content) is the residual non-volatile content mass after placing an arbitrary mass of acrylic resin solution in a petri dish and drying it in an explosion-proof oven at 120°C for 4 hours, expressed as a percentage of the mass of the solution initially measured. The weight-average molecular weight Mw was measured using a GPC device with two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns, tetrahydrofuran as the eluent, and standard polystyrene conversion under the conditions of a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40°C, and a flow rate of 1 mL / min.
[0123] [Preparation of acrylic resin solutions (1) to (5)] (Acrylic resin solution (1)) A monomer mixture prepared by diluting 42.5 parts by mass of n-butyl acrylate, 5 parts by mass of 2-ethylhexyl acrylate, 20 parts by mass of methyl acrylate, 30 parts by mass of 2-methoxyethyl acrylate, 1.0 part by mass of 2-hydroxyethyl acrylate, and 1.5 parts by mass of acrylic acid with ethyl acetate was charged into a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer, and the air in the vessel was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 55° C. Then, a solution of azobisisobutyronitrile dissolved in ethyl acetate as a polymerization initiator was added so that the amount of azobisisobutyronitrile was 0.3 parts by mass per 100 parts by mass of the total amount of monomers. After the addition of the polymerization initiator, the temperature was kept at 55°C for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54-56°C. When the concentration of the acrylic resin reached 35%, the addition of ethyl acetate was stopped, and the temperature was kept at 55°C for 12 hours from the start of the addition of ethyl acetate. Then, ethyl acetate was added to adjust the concentration of the acrylic resin to 20%, and an acrylic resin solution (1) was prepared. The weight average molecular weight Mw of the obtained acrylic resin is shown in Table 1.
[0124] (Acrylic resin solution (2)~(5)) Acrylic resin solutions (2) to (5) were obtained in the same manner as in the preparation of acrylic resin solution (1) except for using the monomer compositions shown in Table 1. The weight average molecular weights Mw of the obtained acrylic resins are shown in Table 1.
[0125] [Preparation of Pressure-Sensitive Adhesive Compositions (1) to (15)] (Adhesive composition (1)) To 100 parts by mass of the solid content of the acrylic resin solution (1) obtained above, 0.5 parts by mass of a crosslinking agent (effective ingredient basis) of "D-103" (a solution of an ethyl acetate adduct of tolylene diisocyanate (solid content concentration 75% by mass) made by Mitsui Chemicals, Inc. under the trade name of "D-103" (effective ingredient basis) was added as a silane compound, 0.5 parts by mass of a silane compound (3-glycidoxypropyltrimethoxysilane) made by Shin-Etsu Chemical Co., Ltd. under the trade name of "KBM-403" (effective ingredient basis) was added as an ionic compound, and 0.54 parts by mass of tributylmethylammonium bis(trifluoromethanesulfonyl)imide was added as an active ingredient basis. Ethyl acetate was further added so that the solid content concentration became 14%, to obtain a pressure-sensitive adhesive composition (1).
[0126] (Adhesive compositions (2) to (15)) Pressure-sensitive adhesive compositions (2) to (15) were obtained in the same manner as in the preparation of pressure-sensitive adhesive composition (1), except that the acrylic resin solutions and ionic compounds shown in Table 2 were used and the amounts of the ionic compounds on an active ingredient basis were set to the amounts shown in Table 2 (amount relative to 100 parts by mass of the solid content of the acrylic resin solution).
[0127] [Preparation of adhesive sheets (1) to (15)] (Adhesive sheet (1)) The adhesive composition (1) obtained above was applied to the release-treated surface of a release film (1) (manufactured by Mitsubishi Chemical Corporation, product name "MRV38 (V04)", thickness: 38 μm) using an applicator so that the thickness after drying would be 15 μm, and then dried at a temperature of 100° C. for 1 minute to obtain an adhesive layer (1) having a thickness of 15 μm. A release film (2) (manufactured by Mitsubishi Chemical Corporation, product name "MRF38", thickness: 38 μm) was laminated on the opposite side of the obtained adhesive layer (1) to the release film (1) so that the release-treated surface was on the adhesive layer (1) side. The obtained laminate was left to stand in an environment of a temperature of 23° C. and a relative humidity of 60% for 7 days or more to obtain an adhesive sheet (1).
[0128] (Adhesive sheets (2)~(15)) Adhesive sheets (2) to (15) were obtained in the same manner as in the preparation of the adhesive sheet (1) except that adhesive compositions (2) to (15) were used.
[0129] [Table 1] BA: n-butyl acrylate 2EHA: 2-ethylhexyl acrylate MA: Methyl acrylate MEA: 2-Methoxyethyl acrylate HEA: 2-hydroxyethyl acrylate AA: Acrylic acid
[0130] [Table 2]
[0131] [Preparation of polarizer (1)] A 30 μm thick polyvinyl alcohol resin film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched vertically by about 5 times by dry stretching, and then, while maintaining tension, was immersed in pure water at a temperature of 60° C. for 1 minute, and then immersed in an aqueous solution at a temperature of 28° C. in which the mass ratio of iodine / potassium iodide / water was 0.05 / 5 / 100 for 60 seconds. Then, it was immersed in an aqueous solution at a temperature of 72° C. in which the mass ratio of potassium iodide / boric acid / water was 8.5 / 8.5 / 100 for 300 seconds. It was then washed with pure water at a temperature of 26° C. for 20 seconds, and then dried at a temperature of 65° C. to obtain a polarizer (1) that is a linearly polarizing layer having a thickness of 12 μm in which iodine is adsorbed and aligned on the polyvinyl alcohol resin film.
[0132] [Preparation of the first protective film] A triacetyl cellulose (TAC) film (thickness: 25 μm) was prepared as the first protective film (1). Also, a triacetyl cellulose (TAC) film (thickness: 25 μm) having a hard coat layer of 7 μm on one side thereof (total thickness: 32 μm) was prepared as the first protective film (2).
[0133] [Preparation of the second protective film] A cycloolefin resin (COP) film (thickness: 13 μm) was prepared as the second protective film (1). A triacetyl cellulose (TAC) film (thickness: 20 μm) was prepared as the second protective film (2). A triacetyl cellulose (TAC) film (thickness: 25 μm) was prepared as the second protective film (3).
[0134] [Preparation of polarizing plate (1)] One side of the surface of the first protective film (1) and the second protective film (1) was subjected to a corona treatment. A water-based adhesive was applied to one side of the polarizer (1), and the first protective film (1) was attached to it. A water-based adhesive was applied to the other side of the polarizer (1), and the second protective film (1) was attached to it. Then, it was dried to obtain a polarizing plate (1). The water-based adhesive was prepared by dissolving 3 parts of carboxyl group-modified polyvinyl alcohol (trade name "KL-318" obtained from Kuraray Co., Ltd.) in 100 parts of water, and adding 1.5 parts of a polyamide epoxy-based additive, which is a water-soluble epoxy resin (trade name "Sumirez Resin 650 (30)" manufactured by Taoka Chemical Co., Ltd., an aqueous solution with a solid content concentration of 30%). As a result, a polarizing plate (1), which is a linear polarizing plate consisting of the first protective film (1) / adhesive layer / polarizer (1) / adhesive layer / second protective film (1), was obtained.
[0135] [Preparation of polarizing plate (2)] One surface of each of the first protective film (1) and the second protective film (2) was subjected to a corona treatment. A water-based adhesive was applied to one surface of the polarizer (1), and the first protective film (1) was attached. A water-based adhesive was applied to the other surface of the polarizer (1), and the second protective film (2) was attached. This was then dried to obtain a polarizing plate (2). As a result, a polarizing plate (2) was obtained, which is a linear polarizing plate consisting of the first protective film (1) / adhesive layer / polarizer (1) / adhesive layer / second protective film (2).
[0136] [Preparation of polarizing plate (3)] One surface of each of the first protective film (2) and the second protective film (3) was subjected to a corona treatment. A water-based adhesive was applied to one surface of the polarizer (1), and the first protective film (2) was attached to it. A water-based adhesive was applied to the other surface of the polarizer (1), and the second protective film (3) was attached to it. This was then dried to obtain a polarizing plate (3). As a result, a polarizing plate (3) was obtained, which is a linear polarizing plate consisting of the first protective film (2) / adhesive layer / polarizer (1) / adhesive layer / second protective film (3).
[0137] [Fabrication of phase shifter (1)] (1) Preparation of Laminate A (1-1) Preparation of composition A for forming photoalignment film The photo-alignment material (weight average molecular weight: 50,000, m:n = 50:50) having the following structure was produced according to the method described in JP 2021-196514 A. Two parts of the photo-alignment material and 98 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80 ° C. for 1 hour to prepare a composition A for forming a photo-alignment film. Photoalignable materials: [ka]
[0138] (1-2) Preparation of polymerizable liquid crystal compound The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) having the structures shown below were prepared. The polymerizable liquid crystal compound (A1) was prepared in the same manner as described in JP-A-2019-003177. The polymerizable liquid crystal compound (A2) was prepared in the same manner as described in JP-A-2009-173893. Polymerizable liquid crystal compound (A1): [ka] Polymerizable liquid crystal compound (A2): [ka]
[0139] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (A1) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.
[0140] (1-3) Preparation of Retardation Film-Forming Composition A The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of a photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) were added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13%. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film-forming composition A.
[0141] (1-4) Preparation of Retardation Film A The photo-alignment film-forming composition A was applied to a biaxially oriented polyethylene terephthalate (PET) film (Diafoil; manufactured by Mitsubishi Plastics, Inc.) as the substrate A using a bar coater. The resulting coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to form a dry film. Thereafter, the film was irradiated with 100 mJ of polarized ultraviolet light (based on 313 nm) using a UV irradiation device (SPOT CURE SP-9; manufactured by Ushio Inc.) to obtain a photo-alignment film A. The thickness of the photo-alignment film A measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100 nm.
[0142] The above-mentioned retardation film-forming composition A was applied onto the obtained photo-alignment film A using a bar coater to form a coating film. This coating film was dried by heating at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.), the exposure amount was 500 mJ / cm2 in a nitrogen atmosphere.2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film A in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, thereby obtaining a laminate A consisting of substrate A / photo-alignment film A / retardation film A. The thickness of retardation film A was 2.0 μm as measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation.
[0143] The surface of retardation film A of laminate A was subjected to corona treatment, and the laminate was attached to glass via a 25 μm-thick adhesive layer, and then substrate A was peeled off and removed. The in-plane retardation values of the laminate of photoalignment film A / retardation film A for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from Cauchy's dispersion formula obtained from the measurement results of the in-plane retardation values for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. As a result, the in-plane retardation values were Re(450)=122 nm, Re(550)=140 nm, and Re(650)=144 nm, and the relationship between the in-plane retardation values at each wavelength was as follows: Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.)
[0144] (2) Preparation of Laminate B (2-1) Preparation of composition B for forming alignment layer A composition B for forming an alignment film was obtained by adding 2-butoxyethanol to a commercially available alignment polymer, Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), so that the solid content was 1%.
[0145] (2-2) Preparation of Retardation Film-Forming Composition B 100 parts of a polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan) having the structure shown below, 0.1 parts of a leveling agent "BYK-361N" (manufactured by BYK-Chemie), and 2.5 parts of a photopolymerization initiator "Omnirad907" (manufactured by IGM Resin BV) were mixed. Furthermore, 400 parts of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the resulting mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film forming composition B. Polymerizable liquid crystal compound LC242: [ka]
[0146] (2-3) Preparation of retardation film B A cycloolefin resin (COP) film (ZF14, manufactured by Zeon Corporation) was used as the substrate B, and one side of the film was subjected to corona treatment using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.), and the composition for forming an alignment film B was applied to the surface of the film using a bar coater and dried at 90° C. for 1 minute. The thickness of the resulting alignment film B was measured with a laser microscope and found to be 30 nm.
[0147] The retardation film-forming composition B was applied onto the obtained alignment film B using a bar coater and dried at 90° C. for 1 minute to obtain a dried film. The retardation film was exposed to light at a dose of 1000 mJ / cm 2 under a nitrogen atmosphere using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.). 2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film B, thereby obtaining a laminate B consisting of a substrate B / alignment film B / retardation film B. The thickness of the retardation film B, as measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation, was 450 nm.
[0148] When measuring the retardation value of laminate B, Re(550) = 1 nm and Rth(550) = -75 nm. Laminate B had optical properties represented by nx ≒ ny < nz. Since the retardation value of COP at a wavelength of 550 nm is approximately 0, it has no influence on the said optical properties.
[0149] (3) Preparation of the phase element (1) (3-1) Preparation of the active energy ray-curable adhesive (1) After blending and mixing the following components, defoaming was carried out to prepare the active energy ray-curable adhesive (1) (hereinafter simply referred to as "adhesive (1)"). (Cationic polymerizable compound) · 3’,4’-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation): 70 parts · Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts · 2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts (Photo cationic polymerization initiator) · Trade name: CPI-100 (manufactured by San-Apro Ltd., 50% propylene carbonate solution): 4.5 parts (substantially 2.25 parts of solid content) (Photosensitizer assistant) · 1,4-Diethoxynaphthalene: 2 parts
[0150] (3-2) Preparation of the phase element (1) The retardation film A of the laminate A and the retardation film B of the laminate B were each subjected to a corona treatment. An adhesive was applied to the corona-treated surface of either the retardation film A or the retardation film B, and the laminate A and the laminate B were bonded together. The adhesive was the above-mentioned adhesive (1). The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was carried out once using the above-mentioned corona treatment device under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The adhesive (1) was cured by irradiating ultraviolet rays from the laminate A side, forming an adhesive layer (1) having a thickness of 1.5 μm. The ultraviolet rays were UVA with a wavelength of 320 nm to 390 nm at 420 mJ / cm. 2 In this manner, a retarder (1) with a substrate was produced, which was composed of substrate A / photo-alignment film A / retardation film A / adhesive layer (1) / retardation film B / alignment film B / substrate B.
[0151] [Preparation of Interlayer Adhesive Layer (1)] An interlayer adhesive layer (1) was prepared by the following procedure: The interlayer adhesive layer (1) is mainly used as an adhesive layer between a linear polarizer and a phase shifter in the examples described later.
[0152] (1) Preparation of acrylic resin solution for interlayer adhesive (1) A mixed solution of 100 parts of ethyl acetate, 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, and 0.5 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while raising the internal temperature to 55 ° C. Then, a solution of 0.12 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56 ° C., and the addition of ethyl acetate was stopped when the concentration of the acrylic resin reached 35% by mass, and the temperature was kept at this temperature until 6 hours had elapsed from the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20% by mass, and an acrylic resin solution (1) for interlayer adhesive was prepared. The weight average molecular weight Mw of the obtained acrylic resin was 1.7 million. The Mw was measured in terms of standard polystyrene using two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns in a GPC apparatus, tetrahydrofuran as an eluent, a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40°C, and a flow rate of 1 mL / min.
[0153] (2) Preparation of Interlayer Adhesive Composition (1) To 80 parts of the solid content of the acrylic resin solution for interlayer adhesive (1) obtained in (1) above, 20 parts (solid content) of a bifunctional acrylate (obtained from Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts of a crosslinking agent (manufactured by Mitsui Chemicals: product name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75 mass%)) based on active ingredients, 1.5 parts of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: product name "Irgacure 500"), and 0.3 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.: product name "KBM-403") were added, and ethyl acetate was further added so that the solid content concentration became 13%, to obtain an interlayer adhesive composition (1).
[0154] A-DOG is a diacrylate of an acetal compound of hydroxypivalaldehyde and trimethylolpropane and has the structure of the following formula. [Chemical formula]
[0155] (3) Preparation of the interlayer adhesive layer (1) The interlayer adhesive composition (1) prepared in the above (2) was applied to the release-treated surface of a release film made of a polyethylene terephthalate film [manufactured by Mitsubishi Chemical Corporation: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness after drying was 5 μm, and dried at 100°C for 1 minute to prepare an interlayer adhesive layer (adhesive sheet). Next, the surface of the obtained adhesive layer on the side opposite to the release film side was bonded to the release-treated surface of a release film made of a polyethylene terephthalate film [manufactured by Mitsubishi Chemical Corporation: MRF (thickness: 38 μm)]. Subsequently, ultraviolet rays were irradiated under the following conditions to prepare the interlayer adhesive layer (1). The storage elastic modulus G' of the interlayer adhesive layer (1) at a temperature of 85°C was 0.125 MPa. [UV irradiation conditions] Fusion UV lamp system (manufactured by Fusion UV Systems) using H bulb · Integrated light amount of UV wavelength region UVA 250 mJ / cm 2 (Measurement value by UV Power PuckII manufactured by FusionUV)
[0156] [Preparation of the circular polarizing plate (1)] The surface of the second protective film (1) of the polarizing plate (1) and the surface exposed by peeling off the substrate A of the retarder (1) were each subjected to a corona treatment. The corona treatment was performed once using the corona treatment device, AGF-B10 manufactured by Kasuga Electric Co., Ltd., under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface of the polarizing plate (1) and the corona-treated surface of the retarder (1) were bonded together via the interlayer adhesive layer (1). Then, the substrate B of the retarder (1) was peeled off to obtain a circular polarizing plate (1) including the first protective film (1) / adhesive layer / polarizer (1) / adhesive layer / second protective film (1) / interlayer adhesive layer (1) / photo-alignment film A / retardation film A / adhesive layer (1) / retardation film B / alignment film B in this order.
[0157] [Preparation of circular polarizing plate (2)] The surface of the second protective film (2) of the polarizing plate (2) and the surface exposed by peeling off the substrate A of the retarder (1) were each subjected to a corona treatment. The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was performed once using the corona treatment device under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface of the polarizing plate (2) and the corona-treated surface of the retarder (1) were bonded together via the interlayer adhesive layer (1). Then, the substrate B of the retarder (1) was peeled off to obtain a circular polarizing plate (2) including the first protective film (1) / adhesive layer / polarizer (1) / adhesive layer / second protective film (2) / interlayer adhesive layer (1) / photo-alignment film A / retardation film A / adhesive layer (1) / retardation film B / alignment film B in this order.
[0158] [Preparation of circular polarizing plate (3)] The surface of the second protective film (3) of the polarizing plate (3) and the surface exposed by peeling off the base material A of the retarder (1) were each subjected to a corona treatment. The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was performed once using the corona treatment device under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface of the polarizing plate (3) and the corona-treated surface of the retarder (1) were bonded together via the interlayer adhesive layer (1). Then, the base material B of the retarder (1) was peeled off to obtain a circular polarizing plate (3) including the first protective film (2) / adhesive layer / polarizer (1) / adhesive layer / second protective film (3) / interlayer adhesive layer (1) / photo-alignment film A / retardation film A / adhesive layer (1) / retardation film B / alignment film B in this order.
[0159] [Table 3]
[0160] [Preparation of polarizing plate with adhesive] Example 1 The release film (2) was peeled off from the adhesive sheet (1), and the exposed adhesive surface was subjected to corona treatment. The retardation film B surface of the circular polarizing plate (1) was then bonded to this corona-treated surface to obtain the adhesive-attached circular polarizing plate of Example 1.
[0161] (Examples 2 to 15 and Comparative Examples 1 to 9) Polarizing plates with adhesive of Examples 2 to 15 and Comparative Examples 1 to 9 were obtained in the same manner as in the production of the circular polarizing plate with adhesive of Example 1, except that the circular polarizing plate and adhesive sheet shown in Table 4 were used.
[0162] [Metal corrosion prevention evaluation] A glass substrate with a metal layer (manufactured by Geomatec Co., Ltd.) was prepared by forming an alloy layer of titanium and aluminum with a thickness of about 500 nm on the surface of alkali-free glass by sputtering. The circular polarizing plate with adhesive obtained above was cut into a size of 30 mm x 30 mm, the release film (1) was peeled off, and the exposed adhesive surface was attached to the metal layer, and autoclaved at a temperature of 50 ° C and a pressure of 0.49 MPa to prepare a test piece for metal corrosion evaluation. This test piece for metal corrosion evaluation was stored for 100 hours in an environment of a temperature of 85 ° C and a relative humidity of 98%, and then the state of the metal layer of the test piece was observed from the polarizing plate side surface by applying light from the glass side of the glass substrate with a metal layer. When the area of the metal layer to which the test piece was attached at this time was A1 and the area of the part of the metal layer to which the test piece was attached that was transmitting light due to corrosion was A2, the proportion A of the corroded part represented by the following formula was obtained. C The corrosion resistance [%] was calculated. If this value is 1.8 or less, it is considered that metal corrosion is appropriately suppressed, more preferably 1.5 or less, and even more preferably 1.15 or less, it can be said that metal corrosion is further suppressed. The results are shown in Table 4.
number
[0163] [Adhesive strength evaluation] The release film (2) was peeled off from the adhesive sheet obtained above, and the exposed adhesive surface was laminated with a PET film (thickness: 50 μm) to obtain a PET film with adhesive. The obtained PET film with adhesive was cut into a size of 25 mm × 120 mm, the release film (1) was peeled off, and the exposed adhesive surface was laminated with alkali-free glass, and then autoclaved at a temperature of 50 ° C and a pressure of 0.49 MPa to obtain a test piece for adhesive strength evaluation. After storing this test piece for adhesive strength evaluation at a temperature of 23 ° C and a relative humidity of 60% for 24 hours, the PET film and adhesive layer were peeled off from the alkali-free glass using an autograph (manufactured by Shimadzu Corporation, product name "AGS-X (50N)") at a peel angle of 180 ° and a peel speed of 0.3 m / min, the test force was averaged over the peeled section, and this was determined as the adhesive strength. If the adhesive strength is 1 N / 25 mm or more, problems such as peeling during impact testing can be appropriately suppressed, and more preferably, if the adhesive strength is 3 N / 25 mm or more, and even more preferably, if the adhesive strength is 5 N / 25 mm or more, problems can be further suppressed. The results are shown in Table 4.
[0164] [Surface resistance evaluation] The release film (2) was peeled off from the adhesive sheet obtained above, and the exposed adhesive surface was bonded to a PET film (thickness: 50 μm) to obtain a PET film with adhesive. The obtained PET film with adhesive was cut to a size of 40 mm × 40 mm, the release film (1) was peeled off, and the probe of a surface resistance measurement device (manufactured by Mitsubishi Chemical Corporation, product name "Hi-resta-up MCP-HT450") was brought into contact with the exposed adhesive surface to measure the surface resistance. The measurement conditions were an applied voltage of 100 V and an application time of 30 seconds. Note that under the measurement conditions described above, the surface resistance was 1.0 × 10 12 If the resistance is more than Ω / □, it is not possible to measure and is indicated as OVER. The surface resistance is 1.0×10 13 When the resistance is Ω / □ or less, it is possible to suppress the occurrence of problems due to charging when the release film is peeled off, and more preferably, it is 1.0×10 12 Ω / □ or less, more preferably 5.0×10 11 By keeping the resistance to Ω / □, it is possible to suppress problems caused by static electricity. The results are shown in Table 4.
[0165] [Table 4] [Explanation of symbols]
[0166] 1... optical film with adhesive, 10... optical film, 20... adhesive layer, 30... metal layer, 40... substrate, 50... resin layer, 100, 200, 300... optical laminate.
Claims
1. A pressure-sensitive adhesive composition comprising a (meth)acrylic resin (A-1) and an ionic compound (A-2), The (meth)acrylic resin (A-1) contains a structural unit derived from an alkoxyalkyl (meth)acrylate in an amount of 10% by mass or more and 40% by mass or less based on the total amount of structural units constituting the (meth)acrylic resin (A-1), The pressure-sensitive adhesive composition, wherein the ionic compound (A-2) is an ionic compound comprising an anion moiety represented by the following formula (A-2-1) and an organic cation: [Formula 1] [In the formula, R 4 and R 5 each independently represents a perfluoroalkyl group having 1 to 4 carbon atoms, or R 4 and R 5 and represents a perfluoroalkylene group having 1 to 8 carbon atoms formed by bonding with each other.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the structural unit derived from an alkoxyalkyl (meth)acrylate includes a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-1): [chemical 2] [In the formula, R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkylene group having 1 to 4 carbon atoms; R 3 represents an alkyl group having 1 to 4 carbon atoms.
3. The pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylic resin (A-1) contains a structural unit derived from a carboxyl group-containing monomer in an amount of 0.6 mass% to 10 mass% based on the total amount of structural units constituting the (meth)acrylic resin (A-1).
4. The pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylic resin (A-1) contains a structural unit derived from a (meth)acrylic acid ester represented by the following formula (A-1-2): [C3] [In the formula, R 6 represents a hydrogen atom or a methyl group, R 7 represents an alkyl group or an aralkyl group having 1 to 14 carbon atoms.
5. The (meth)acrylic resin (A-1) is represented by the formula (A-1-2) and the R 7 is an alkyl group having 1 to 3 carbon atoms, based on the total amount of structural units constituting the (meth)acrylic resin (A-1),
6. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the ionic compound (A-2) is 0.1 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the (meth)acrylic resin (A-1).
7. The pressure-sensitive adhesive composition according to claim 1, wherein the ionic compound (A-2) has a melting point of 23° C. or higher.
8. R of the anion part of the ionic compound (A-2) 4 and R 5 The pressure-sensitive adhesive composition according to claim 1 , wherein each of the groups is a trifluoromethyl group.
9. The pressure-sensitive adhesive composition according to claim 1, wherein the organic cation of the ionic compound (A-2) contains a nitrogen atom.
10. A pressure-sensitive adhesive layer formed using the pressure-sensitive adhesive composition according to any one of claims 1 to 9.
11. The pressure-sensitive adhesive layer according to claim 10, having a thickness of 2 μm or more and 50 μm or less.
12. A polarizing plate with adhesive, comprising the adhesive layer according to claim 10 and a polarizing plate attached thereto.
13. The polarizing plate with adhesive according to claim 12 , wherein the polarizing plate comprises a retarder.
Citation Information
Patent Citations
Polarizing plate
JP1994313807A
Antistatic acrylic adhesive
JP2005206776A
